Expedient production of site specifically nucleobase-labelled or hypermodified RNA with engineered thermophilic DNA polymerases - Brunderová, Mária; Havlíček, Vojtěch; Matyašovský, Ján; Pohl, Radek; Poštová Slavětínská, Lenka; Krömer, Matouš; Hocek, Michal (Nature communications, 2024)
Innovative approaches to controlled nucleobase-modified RNA synthesis are urgently needed to support RNA biology exploration and to synthesize potential RNA therapeutics. Here we present a strategy for enzymatic construction of nucleobase-modified RNA based on primer-dependent engineered thermophilic DNA polymerases - SFM4-3 and TGK. We demonstrate introduction of one or several different base-modified nucleotides in one strand including hypermodified RNA containing all four modified nucleotides bearing four different substituents, as well as strategy for primer segment removal. We also show facile site-specific or segmented introduction of fluorophores or other functional groups at defined positions in variety of RNA molecules, including structured or long mRNA. Intriguing translation efficacy of single-site modified mRNAs underscores the necessity to study isolated modifications placed at designer positions to disentangle their biological effects and enable development of improved mRNA therapeutics. Our toolbox paves the way for more precise dissecting RNA structures and functions, as well as for construction of diverse types of base-functionalized RNA for therapeutic applications and diagnostics.
Keywords: DNA-dependentní DNA-polymerasy; RNA, Messenger; messenger RNA; DNA-Directed DNA Polymerase; RNA; nukleotidy; Nucleotides